Non-apoptotic activation of Drosophila caspase-2/9 modulates JNK signaling, the tumor microenvironment, and growth of wound-like tumors. - Xu, D.C.; Wang, L.; Yamada, K.M.; Baena-Lopez, L.A. (Cell reports, 2022)
Resistance to apoptosis due to caspase deregulation is considered one of the main hallmarks of cancer. However, the discovery of novel non-apoptotic caspase functions has revealed unknown intricacies about the interplay between these enzymes and tumor progression. To investigate this biological problem, we capitalized on a Drosophila tumor model with human relevance based on the simultaneous overactivation of the EGFR and the JAK/STAT signaling pathways. Our data indicate that widespread non-apoptotic activation of initiator caspases limits JNK signaling and facilitates cell fate commitment in these tumors, thus preventing the overgrowth and exacerbation of malignant features of transformed cells. Intriguingly, caspase activity also reduces the presence of macrophage-like cells with tumor-promoting properties in the tumor microenvironment. These findings assign tumor-suppressing activities to caspases independent of apoptosis, while providing molecular details to better understand the contribution of these enzymes to tumor progression.